2012
DOI: 10.1371/journal.pone.0034989
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Performance of Prey Targeting in Pit Vipers with Contralaterally Occluded Infrared and Visual Senses

Abstract: Both visual and infrared (IR) senses are utilized in prey targeting by pit vipers. Visual and IR inputs project to the contralateral optic tectum where they activate both multimodal and bimodal neurons. A series of ocular and pit organ occlusion experiments using the short-tailed pit viper (Gloydius brevicaudus) were conducted to investigate the role of visual and IR information during prey targeting. Compared with unoccluded controls, snakes with either both eyes or pit organs occluded performed more poorly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The sensory field of the IR‐device substantially overlaps that of the eye. The sensory field overlap is also reflected by the neural spatiotopic maps for both systems (Hartline et al, ) as well as in the targeting areas (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The sensory field of the IR‐device substantially overlaps that of the eye. The sensory field overlap is also reflected by the neural spatiotopic maps for both systems (Hartline et al, ) as well as in the targeting areas (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pit vipers possess four sensors (e.g., two eyes and two pits) for detecting electromagnetic radiation, each seemingly of equal weight for decision making. A previous study showed that compared to controls, about 75% of prey attacks were successful when one eye and one pit were occluded on the same side of the face, or when either both eyes or both pit organs were occluded (Chen et al, ). These results suggest that the eye and pit on the same side of the head work in concert for targeting prey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations